Penerapan Model Pembelajaran Kooperatif Tipe Stad untuk Meningkatkan Hasil Belajar IPA di Kelas V SD GMIST Zaitun Lapepahe - Christin Natalia Johanis (Peneliti.net, 2023)
Based on observations that have been carried out at SD GMIST Zaitun Lapepahe in class V, it shows that learning outcomes are achieved in the science learning process. This is because there are still students who are noisy and do not participate in learning so that their learning outcomes are low and the teacher only uses the group work method. . The number of students who got low scores was 21 people and those who got high scores were 15 people. This study aims to improve science learning outcomes through the application of the SDAD type cooperative learning model for fifth grade students at SD GMIST Zaitun Lapepahe. This research was conducted using classroom action research which refers to the research design put forward by Kemmis and Mc. Tangart (zainal Aqib, 2006: 31) which consists of 4 stages, namely: 1. Planning, 2. Action, 3. Observation 4. Reflection. Different results were obtained where in the first cycle the student learning outcomes reached 66.8% while in the second cycle the learning outcomes reached 83.5% so that the implementation of the action was declared successful. Based on this research it can be concluded that the application of the SDAD type cooperative learning model can improve student learning outcomes class V SD GMIST Zaitun Lapepahe. For this reason, it is suggested that science teachers should use the SDAD Type Cooperative learning model so that students are enthusiastic about learning activities.